Interpersonal Communication Assessment Scale: psychometric study of the Portuguese version - Lopes, Rosa Cristina Correia (2013)
This paper is a report of a study of the psychometric properties of the Portuguese version of the Interpersonal Communication Assessment Scale (ICAS) related to the nursing education. The interpersonal communication in Health care in general and in nursing care in particularly serves to transmit messages between the elements involved, in order to created a meaning in their interaction. The essence of nursing care is focused on interpersonal communication between nurse and the patient. The basis of professional competence in nursing is on personal qualities, the personality of the nurse, which is decisive for the acquisition of training and experience. The validation of ICAS was developed in four steps: translation, back translation, comparing the two versions and evidence of the validity of the new version. The psychometric study was carried out using the Statistical Package for Social Sciences. The non-probabilistic convenience sample was constituted of 156 students of the 2nd year of the Degree Course of Nursing (2008-2009). The psychometric study revealed high values: Cronbach alpha (ICAS: 0.939; advocacy: 0.857; therapeutic: 0.890; use of self and validation: 0.795), Pearson correlation (r=0.740, p=0.000), test of sphericity Barlett (2190.278, p=0.000) and KMO measure of adequacy (0.910). In general way the psychometric characteristics of the ICAS-Portuguese version are comparable to that version original. The reliability of results is reflected in high levels of internal consistency of the ICAS and excellent temporal stability, allowing considers it as an appropriate tool in the evaluation of interpersonal communication skills.